Circular economy and sustainable development in primary education - Kosta, Aikaterini D.; Keramitsoglou, Kiriaki M.; Tsagarakis, Konstantinos P. (Frontiers in Sustainability, 2025)
Acknowledging the importance of implementing environmental policies at the ground level, research reveals slow knowledge diffusion and behavioral challenges affecting policy outcomes. Despite the global consensus, national sustainable development policies often remain incomplete. Focusing on education, while the circular economy (CE) is extensively discussed in higher education, it remains notably absent in primary education curriculums. Drawing on the responses of 61 primary education teachers, this study (i) locates the lack of integration of circularity and sustainability concepts at Greek State primary schools, underscores the necessity for their inclusion into the curriculum more systemically and systematically to address disparities, and suggests solutions for a more comprehensive environmental education; (ii) unveils primary educators’ awareness and positivity toward teaching-learning of sustainable development goals and education for a CE and emphasizes on their ongoing support, education, and training.